Utilization of Preventive Measures in Avoidance of Covid 19 Pandemic Among Health Educators in Federal and State Owned Colleges of Education in Delta State - I. N. , Okudaye (International Journal For Research In Educational Studies, 2021)
This study was undertaken to investigate utilization of preventive measures in avoidance of COVID 19 pandemic among health educators in federal and state owned colleges of education in delta state. The study made use of descriptive survey design. The population was 77 health educators in the four Federal and State Colleges of Education in Delta State. The entire 77 health educators in the four Federal and state owned colleges of education in Delta state were used in the study because of their fewness. The instruments used in the study were instrument titled “Utilization of Preventive Measures in Avoidance of Covid 19 Pandemic Questionnaire (UPMACPQ)”. From the 77 copies of the questionnaires administered, 73 copies were retrieved. Male health educators were 51 and female health educators were 22. In terms of experienced, 49 experienced health educators were used while 24 inexperienced health educators were as well used in the investigation. Mean rating and standard deviation were utilized to answer the six research questions. z test was employed to test the two null hypotheses created to guide the investigation at 0.05 levels of significance. Findings showed that the forms of preventive measures for avoidance of COVID 19, factors responsible for utilization of preventive measures against COVID 19 pandemic, the consequences of COVID 19 pandemic, the management strategies that can be employed to encourage the utilization of preventive measures against COVID 19 pandemic among health educators in federal and state owned colleges of education in Delta state were high as the ratings were high. The difference between male and female health educators, experienced and inexperienced Health educators on the Utilization of Preventive Measures against COVID 19 pandemic in federal and state owned colleges of education in Delta state were high as the ratings were high. There was no significant difference between male and female health educators, experienced and inexperienced health educators on the utilisation of preventive measures in the period of COVID 19 pandemic among health educators in federal and state owned colleges of education in Delta state. It was concluded that The forms of preventive measures for avoidance of COVID 19 pandemic, the factors responsible for utilisation of preventive measures against COVID 19 pandemic, the consequences of COVID 19 pandemic, the management strategies that can be employed to encourage the utilisation of preventive measures against COVID 19 pandemic among health educators in federal and state owned colleges of education in Delta state was high. The difference between male and female, experienced and inexperienced Health educators on the Utilisation of Preventive Measures against COVID 19 pandemic in federal and state owned colleges of education in Delta state was high. Male and female , Experienced and inexperienced health educators do not differ significantly on the utilisation of preventive measures in the period of COVID 19 pandemic among health educators in federal and state owned colleges of education in Delta state. It was recommended in the study that the college of Education administrators that should organise the required enlightenment plans in order to offer current data and convey the finest practice to control the COVID-19 infection. Training should be offered for the health educators by the Colleges of Education authorities on procedures to avert COVID 19 in their job performance.